Investigating Institutional Investors' Behaviours toward Cash Waqf Linked Sukuk (CWLS) using DTPB - Nurhaida, Dida; Jasfar, Farida; Ismal, Rifki; Jayaprawira, Acep Riana (International Journal of Islamic Economics and Finance (IJIEF), 2023)
Cash Waqf Linked Sukuk (CWLS) is a newly developed social investment instrument to stimulate Indonesia's productive waqf movement. CWLS has numerous commercial and social benefits and worship values. However, despite these advantages, it takes a long time for CWLS to collect funds due to various challenges and inadequate investors' response rate, which is still far from expectation. Thus, this study looks into the contributing factors and antecedence that entail and determine the decision of an institutional investor to invest. The theoretical framework applied the decomposed theory of planned behavior (DTPB). Additionally, it highlights a new perspective by delivering the specific determinants that impact investors' attitudes, moral norms, and perceived behavior control. These factors offer a deep understanding of the association and determine their definite effects on intentions. Based on a survey of 250 respondents, analyzed using partial least squares – structural equation modeling (PLS-SEM), it was found that the proposed hypotheses were accepted. Above all, the important finding is the contribution of attitude as the dominant determinant impacting the investor's intention. It was mainly driven by perceived Ihsan as part of the Muslim religiosity dimension reflecting the spirit to do good. This study's findings provide deeper insight into untested behavior literature. This study will also benefit policymakers, academicians, and future researchers.